5(k-78)+-96=-51

Simple and best practice solution for 5(k-78)+-96=-51 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(k-78)+-96=-51 equation:


Simplifying
5(k + -78) + -96 = -51

Reorder the terms:
5(-78 + k) + -96 = -51
(-78 * 5 + k * 5) + -96 = -51
(-390 + 5k) + -96 = -51

Reorder the terms:
-390 + -96 + 5k = -51

Combine like terms: -390 + -96 = -486
-486 + 5k = -51

Solving
-486 + 5k = -51

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '486' to each side of the equation.
-486 + 486 + 5k = -51 + 486

Combine like terms: -486 + 486 = 0
0 + 5k = -51 + 486
5k = -51 + 486

Combine like terms: -51 + 486 = 435
5k = 435

Divide each side by '5'.
k = 87

Simplifying
k = 87

See similar equations:

| 9x-7x=-30 | | 3.6-x=9 | | -7(q+56)=14 | | 3erty+4erty=5ertyz | | y=6+m(x+5) | | -4=-29u | | -3x+12/2 | | 2/-3x+12 | | 9/5*-30+32 | | j-69/2=9 | | 1+3=x-18 | | 1/2*((5x+6)+(3x))*(4x-3) | | x+(y+5)=-1 | | 5(x-3)=-9(x+1)+29 | | k+1(k^2+5k+6)=0 | | 8X^2-2xy-3y^2=0 | | 9X^2-2xy-3y^2=0 | | 580=3x | | 2(4t-7)/3=-22 | | 2(h+12)/5=10 | | 3x^2-x-13=0 | | 4x^2=-9x-4 | | 12+4(z+3)=3z+2 | | 10+5(z-2)=42+5 | | (12x-8)/4=28 | | y+3=(x-9) | | 12x-8/4=28 | | -13n+4=-12n-12 | | 2(t-7)-8=8 | | 8x-4=9x+9 | | -48-(-15)=x/5 | | -sinx^2+2sinx+1=0 |

Equations solver categories